Studies of Colletotrichum dematium f. sp. truncatum on soybean - Wong, C. F. J.; Wan Nik, Wan Zainun; Lim , Tong Kwee (1983)
Growth and sporulation studies of Colletotrichum dematium var. truncatum were conducted using different media, temperatures and light regimes. Of the seven media employed oat meal agar supported the best mycelial growth, with sporulation best on Czapek Dox agar and potato dextrose agar. Greater mycelial growth was obtained under 12 hours alternating ultraviolet light and continuous light than in darkness. Sporulation was highest under 12 hours alternating light treatment. The optimum temperature for growth and sporulation was 25° C while germination was optimum at 20° C. Pathogenicity studies in the glasshouse showed that seedlings of cultivar 66D-16 were most susceptible while cultivar 66F-4A most resistant. Inoculation studies on detached green pods indicated that 66D-16 was most susceptible and Palmetto most resistant. An in vitro efficacy test of five fungicides against the fungus showed that Topsin M was the most toxic with an EDso of 2.2 pgjml.